Strategies for Teaching Abstract Vocabulary in Thai for Early Childhood Learners through Aesop’s Fables Featuring Human Characters - Choeirod, Ratchaneechay; Jettra, Phramaha Sarayut; Buddanang, Phramaha Athiwat; Sarakool, Phramaha Charun; Suwunla, Kitti (Journal for Developing the Social and Community, 2026)
Background and Objectives: Early childhood learners are at a developmental stage in which understanding abstract vocabulary is still emerging. Therefore, Thai language instruction should employ learning materials that help connect word meanings with learners’ everyday experiences. Aesop’s fables, in particular, provide simple and accessible narratives that are suitable for young learners. This study aims to examine strategies for teaching abstract vocabulary in Thai for early childhood learners through Aesop’s fables featuring human characters. Methodology: This study employed a qualitative research approach by analyzing the content of 13 Aesop’s fables featuring human characters. The fables were selected through purposive sampling to ensure relevance to the learning context of early childhood learners. Results: The findings revealed that strategies for teaching abstract vocabulary can be categorized into four types: (1) teaching through characters’ behaviors, (2) teaching through cause-and-effect relationships, (3) teaching through problem-based situations, and (4) teaching through concrete comparisons. These strategies help early childhood learners understand abstract vocabulary by linking meanings to experiences, events, and tangible objects Conclusion: The results indicate that Aesop’s fables featuring human characters can serve as effective instructional media for teaching abstract vocabulary when teachers use appropriate explanatory strategies and actively guide meaning construction in a systematic manner.